Electrochemiluminescence/Electrochemistry Dual-Mode Synchronous Sensing of Pb2+ Based on G4–hemin DNAzyme Complex During One-Step Scan - Rukai Wei; Lei Shang; Wei Zhang; Xiaojian Li; Liping Jia; Rongna Ma; Huaisheng Wang (Molecules)
Electrochemiluminescence (ECL)/electrochemistry (EC) dual-mode sensors have garnered significant interest for their enhanced analytical reliability through the cross-verification of dual-signal outputs. However, conventional approaches necessitate two potential scans to acquire ECL and EC signals independently, resulting in temporal and environmental discrepancies between the two detection modes. In this paper, we present a novel synchronous ECL/EC dual-mode sensing platform for lead ion (Pb2+) detection via a one-step potential scan (0.2 to −0.4 V vs. Ag/AgCl) utilizing a G-quadruplex (G4)–hemin DNAzyme complex. This complex synergistically catalyzed the electrochemical reduction of dissolved oxygen, concurrently generating a distinct cathodic ECL emission from Ru(bpy)32+ and a synchronous reduction current peak at −0.25 V. Pb2+ quantification was achieved through its dose-dependent suppression of DNAzyme activity by destabilizing the G4–hemin interaction, thereby proportionally attenuating both ECL intensity and EC signal (reduction current). The integrated sensor demonstrated high sensitivity (detection limits of 1.51 nM for ECL detection and 2.03 nM for EC detection), robust anti-interference capability, and satisfactory reproducibility, with recoveries ranging from 95.5 to 103.1% in environmental water analysis. This work established a paradigm for one-step dual-mode sensor design, offering new prospects for environmental monitoring.